2 - Violence, Identity Mobilization and the Reimagining of Biafra: https://doi.org/10.4314/ad.v34i1.57353 - Ukiwo, Ukoha (Africa Development, 2021)
The events leading to the Nigeria Civil War marked the triumph of force and violence over dialogue and negotiation as a means of conflict resolution. The success of the Nigerian state in imposing a military solution on the preceding political crisis, and then suppressing the ensuing Biafran rebellion, has had a lasting effect on state–society relations. As a result, the state has not refrained from using violence at the slightest provocation against competing and con- flicting ethno-religious groups. The tendency of the state to exercise domina- tion through the deployment of violence implies an ongoing crisis of state he- gemony rather than a resolution of civil unrest. This article argues that state violence was more important than ethnic divisions in triggering the secessionist attempt of Biafra, and has continued to create rather than resolve ethnic divi- sions across the country. The emergence in post-Civil War Nigeria of regimes that perpetrated or permitted mass violence against restive social groups re- mains critical to understanding the contemporary rise of ethno-nationalist move- ments and waning allegiance to the Nigerian state, particularly among the Igbo. The aim of the article is to underscore the understated salience of state violence in the debates on identity and citizenship in multi-ethnic societies.